Antimicrobial dispersion liquid comprising metal fine particles as active ingredient

By coating metal fine particles with ascorbic acid or its derivatives, the dispersion stabilizes and maintains antimicrobial properties, addressing the issue of agglomeration and oxidation in metal particle dispersions.

JP2025018327APending Publication Date: 2025-02-06TOYO SEIKAN GRP HLDG LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023121927
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Metal fine particles in antimicrobial dispersions tend to agglomerate and lose their antimicrobial properties over time when a thickener is added to enhance dispersibility, leading to instability and reduced effectiveness.

Method used

Coating the surface of metal fine particles with ascorbic acid or its derivatives, combined with specific dispersants and thickeners, to stabilize the dispersion and maintain antimicrobial properties over time.

Benefits of technology

The dispersion maintains uniform dispersibility and antimicrobial activity of metal particles for extended periods, preventing oxidation and agglomeration, even when thickeners are present.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018327000001
    Figure 2025018327000001
  • Figure 2025018327000002
    Figure 2025018327000002
  • Figure 2025018327000003
    Figure 2025018327000003
Patent Text Reader

Abstract

To provide a dispersion liquid that ensures the excellent antimicrobial properties of metal fine particles remain stable over a long period, even when incorporating a dispersant and a thickener that enable uniform dispersion of metal fine particles.SOLUTION: A dispersion liquid contains metal fine particles, a dispersant and a thickener. The surfaces of the metal fine particles are at least partially covered with ascorbic acid or a derivative thereof. The dispersant is at least one selected from copolymers and low-molecular-weight compounds with ionic hydrophilic groups and hydrophobic groups.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dispersion liquid containing metal microparticles, and more specifically, to a dispersion liquid containing metal microparticles having at least a portion of their surface coated with ascorbic acid or a derivative thereof, a dispersant, and a thickener, which makes it possible to maintain the metal microparticles in a uniformly dispersed state for a long period of time, while suppressing oxidation of the metal microparticles by the thickener, and thus has excellent antimicrobial properties. [Background technology]

[0002] Materials having antimicrobial properties such as antibacterial and antiviral properties, which contain fine metal particles of silver, copper, or the like as an active ingredient, are provided in various forms, such as dispersions obtained by dispersing fine metal particles in a solvent, paint compositions obtained by incorporating fine metal particles in a binder resin for paint, and resin compositions obtained by incorporating fine metal particles in a thermoplastic resin or a thermosetting resin. For example, the following Patent Document 1 describes an antiviral composition containing fine particles of a monovalent copper compound, a reducing agent, and a dispersion medium, and having a pH of not more than 6. The following Patent Document 2 describes an antiviral coating film having a copper-supported oxide having an average secondary particle size of 80 nm to 600 nm, in which at least one of copper particles and copper compound particles is supported on an oxide particle, barium sulfate having an average secondary particle size of 1 μm to 15 μm, and a water-repellent resin binder.

[0003] However, metal fine particles tend to aggregate and are difficult to disperse uniformly. In particular, when the dispersion is used as an antiviral composition or when it is mixed with a binder resin for paint and used as an antiviral coating film, it has been difficult to efficiently express the antimicrobial properties of the metal fine particles. As a dispersion liquid with improved dispersibility of metal fine particles, the present inventors have proposed a dispersion liquid containing metal fine particles modified with a fatty acid (Patent Documents 3 and 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5194185 [Patent Document 2] JP 2015-205998 A [Patent Document 3] JP 2017-128809 A [Patent Document 4] JP 2018-100255 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the metal microparticle dispersions described in Patent Documents 3 and 4 above, the surface of the metal microparticles is coated with a fatty acid and / or an ester compound of the fatty acid, thereby preventing aggregation of the metal microparticles and enabling the metal microparticles to be uniformly dispersed in the dispersion medium. However, when a thickener that increases the viscosity of the dispersion medium is added for the purpose of further improving the dispersibility of the metal microparticles, the excellent antiviral properties, etc., of the metal microparticles can be expressed immediately after preparation of the dispersion liquid. However, when this dispersion liquid is stored for a long period of time, there are cases in which the effects of the metal microparticles, such as antiviral properties, cannot be obtained.

[0006] Therefore, the object of the present invention is to provide a composition that can stably exhibit the excellent antimicrobial properties of metal microparticles over a long period of time, even when used in combination with a thickener that can exhibit uniform dispersibility of metal microparticles. [Means for solving the problem]

[0007] According to the present invention, there is provided a dispersion liquid containing metal fine particles, a dispersant and a thickener, characterized in that at least a portion of the surface of the metal fine particles is coated with ascorbic acid or a derivative thereof, and the dispersant is at least one selected from a copolymer polymer and a low molecular weight compound having an ionic hydrophilic group and a hydrophobic group.

[0008] In the dispersion of the present invention, (1) The metal fine particles are copper or a copper compound, silver or a silver compound, or a composite thereof; (2) The thickener is an aqueous thickener, and is a polymer or an inorganic mineral containing a vinylpyrrolidone unit; (3) The ascorbic acid or a derivative thereof is contained in an amount of 10 parts by mass or more per 100 parts by mass of the metal fine particles. (4) The thickener is contained in an amount of 50 to 5,000 parts by mass per 100 parts by mass of the metal fine particles. (5) The dispersant comprising the copolymer has a polyoxyethylene skeleton. (6) The dispersant comprising a low molecular weight compound having an ionic hydrophilic group and a hydrophobic group is an anionic surfactant or a cationic surfactant. (7) The dispersant is contained in an amount of 50 to 1000 parts by mass relative to 100 parts by mass of the metal fine particles. (8) The metal fine particles are coated with a fatty acid and / or a fatty acid ester. (9) The content of the metal fine particles is 0.001 to 10% by mass. is preferred.

[0009] The present invention also provides an antibacterial and antiviral agent comprising the above dispersion. The present invention further provides an antimicrobial molded article comprising a layer made of the above dispersion on the surface of a molded article made of any one of a plastic molded article, a nonwoven fabric, a woven fabric, and a knitted fabric. In the antimicrobial molded article of the present invention, it is preferable that the antiviral activity value after one month is 3.0 or more.

[0010] The present invention further provides a method for producing the above dispersion, which is characterized by adding and mixing metal fine particles, ascorbic acid or a derivative thereof, and a dispersant into a dispersion medium to prepare a dispersion containing metal fine particles having at least a portion of their surface covered with the ascorbic acid or a derivative thereof, and then adding and mixing a thickener into the dispersion. Effect of the Invention

[0011] In the dispersion of the present invention, at least a portion of the surface of the metal microparticles is coated with ascorbic acid or a derivative thereof, which makes it possible for the metal microparticles to exhibit their excellent antimicrobial properties for a long period of time even when a dispersant and a thickener are incorporated. Furthermore, since ascorbic acid or a derivative thereof, which is added as a stabilizer, itself has antimicrobial properties, it is possible to exhibit superior antimicrobial properties over a long period of time than those exhibited by metal microparticles alone. Furthermore, by adding a thickener, it is possible to adjust the viscosity of the dispersion liquid, and it is possible to prevent the metal particles from settling and to disperse them uniformly in the dispersion medium. Furthermore, by coating the surface of the metal microparticles with the above-mentioned stabilizer, or further with a fatty acid and / or a fatty acid ester, in combination with the addition of a thickener, the metal microparticles can be dispersed more uniformly in the dispersion liquid without agglomerating, and therefore, even when formed as a coating on the surface of a molded article, a molded article having excellent antimicrobial properties can be provided.

[0012] The above-mentioned effects of the dispersion of the present invention are apparent from the results of the examples described below. That is, in the dispersion containing L-ascorbic acid together with metallic copper particles, as is clear from the difference in zeta potential value from Production Example 5 in which ascorbic acid was not added, the surfaces of the metallic copper particles in the dispersion are coated with ascorbic acid (Production Examples 1 to 4).As a result, even when polyvinylpyrrolidone or montmorillonite was added as a dispersant or thickener, oxidation of the metallic copper particles was suppressed even after one month had passed (Examples 1 to 6), and excellent antiviral properties were exhibited (Examples 7 to 8). In contrast, in the case of dispersions prepared in the same manner as in Examples 1 to 3 except that ascorbic acid was not added, the dispersions turned brown after one month, and it was found that the metallic copper particles had turned into copper oxide (Comparative Examples 1 to 3). Furthermore, when the dispersions prepared one month after the preparation were used, no antiviral properties were obtained (Comparative Example 5).

[0013] In this specification, antimicrobial properties collectively refer to antibacterial properties, antiviral properties, antifungal properties, etc., and refer to the effect of inactivating bacteria, viruses, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (dispersion) In the dispersion liquid of the present invention, it is believed that the metal microparticles decompose proteins of microorganisms such as viruses due to the oxidizing power of active oxygen generated from the metal microparticles, and also denature the proteins by reacting with thiol groups in the proteins, thereby inactivating the viruses, etc. On the other hand, when a dispersant and a thickener are blended into a metal microparticle-containing dispersion to improve the dispersibility of metal microparticles, even if antimicrobial properties are obtained immediately after preparation, the metal microparticles in the dispersion are oxidized over time, and antimicrobial properties cannot be obtained. However, by containing ascorbic acid or a derivative thereof, which has reducing properties, together with the metal microparticles, the disappearance of the metal microparticles exhibiting antimicrobial properties over time is effectively suppressed.

[0015] In other words, in the dispersion liquid of the present invention, at least a portion of the surface of the metal microparticles is coated and protected by ascorbic acid or its derivatives, which have reducing properties, making it possible to maintain the state of the metal microparticles stably for a long period of time without being affected by the dispersant and thickener. The dispersion of the present invention is in the state of a dispersion in which a dispersant, a thickener, and ascorbic acid or a derivative thereof are dispersed in a dispersion medium together with metal fine particles at least partially coated on the surface thereof with ascorbic acid or a derivative thereof. As will be described later, the dispersion can be used as an antiviral agent in this state, or, depending on the type of dispersion medium, a binder resin can be further blended into the dispersion to be used as a paint dispersion.

[0016] In the dispersion of the present invention, it is preferable to contain 10 parts by mass or more of ascorbic acid or a derivative thereof per 100 parts by mass of metal fine particles. By containing ascorbic acid or a derivative thereof in the above range, the surfaces of the metal fine particles are efficiently covered with ascorbic acid or a derivative thereof, and even if a dispersant or a thickener is blended in the dispersion, oxidation of the metal fine particles due to the thickener can be effectively prevented. The upper limit of the content of ascorbic acid or its derivative is not limited as long as the excess ascorbic acid or its derivative not used for coating the surface of the metal fine particles can be uniformly dispersed in the composition, but it is preferable that it is contained in a range of 15 parts by mass or less, 8 parts by mass or less, and particularly 6 parts by mass or less. If the content of ascorbic acid or its derivative is excessive, the appearance of the coating film obtained by applying the dispersion or the coating dispersion containing this dispersion is impaired, so the above range is preferable.

[0017] In addition, in the dispersion of the present invention, it is preferable to contain the thickener in an amount of 50 to 5000 parts by mass, particularly 100 to 1000 parts by mass, per 100 parts by mass of the metal fine particles. By containing the thickener in the above range, it is possible to provide a dispersion in which the metal fine particles are stably and uniformly dispersed for a long period of time. If the amount of the thickener is less than the above range, the effect of the dispersion stability of the metal fine particles obtained by blending the thickener may not be fully obtained, while if the amount of the thickener is more than the above range, the viscosity of the dispersion may become too high, which may impair the appearance of the coating film obtained by applying the dispersion or the coating dispersion containing this dispersion.

[0018] [Metal fine particles] In the dispersion of the present invention, examples of metal fine particles include metals such as copper, silver, gold, zinc, and nickel, and compounds of these metals, but copper or silver, or compounds of these metals, which can exhibit excellent antimicrobial properties, are preferred, and in particular, copper or copper compounds, and among these, copper or monovalent copper compounds are preferred from the viewpoint of excellent antiviral properties. Furthermore, since copper or copper compounds are easily oxidized by thickeners, the present invention can suitably exhibit antimicrobial properties. The metal fine particles preferably have an average primary particle size in the range of 10 to 500 nm, particularly 10 to 200 nm. When the average primary particle size of the metallic copper fine particles is in the above range, it is possible to efficiently exhibit excellent antimicrobial performance. That is, metal fine particles having such a small average primary particle size can efficiently generate active oxygen because the contact rate of the metal fine particles with oxygen is high, and it is possible to exhibit excellent antimicrobial performance. In addition, the metal fine particle powder is composed of primary particles having the above average primary particle size, and the average secondary particle size is preferably in the range of 100 nm to 500 μm, particularly 100 nm to 100 μm, and this allows the metal fine particles obtained in a powder state to be easily dispersed in a dispersion medium, and also provides excellent handling properties such as coatability of the paint dispersion obtained by diluting with a solvent. In this specification, the average primary particle size refers to the average particle size of metal particles with no gaps between them, and the average secondary particle size refers to the average particle size of metal particles packed together. The primary particle size can be measured by a scanning electron microscope (SEM), and the secondary particle size can be measured by dynamic light scattering (DLS).

[0019] The metal fine particles used in the present invention are preferably surface-coated with a fatty acid and / or a fatty acid ester, which, in combination with the above-mentioned stabilizing agent, can further suppress the aggregation and oxidation of the metal fine particles, thereby providing excellent antimicrobial properties and dispersibility. Examples of fatty acids that may be used to coat the surface of the metal microparticles include caprylic acid, capric acid, lauric acid, myristic acid, stearic acid, oleic acid, palmitic acid, n-decanoic acid, para-toic acid, succinic acid, malonic acid, tartaric acid, malic acid, glutaric acid, adipic acid, and acetic acid. These may be used in combination with multiple types of acids, but palmitic acid and stearic acid are particularly preferred. The ester compound coating the surface of the metal microparticles is preferably an ester compound derived from the fatty acids and polyols that are the raw materials in the method for producing metal microparticle powder of the present invention described below, but it is also possible to blend in ester compounds other than those derived from the raw materials, and these may be different ester compounds, but it is preferable that they are of the same type as the ester compounds derived from the raw materials. Suitable ester compounds for coating the surface of metal microparticles include ester compounds of the above-mentioned fatty acids and the polyols described below, such as, but not limited to, diethylene glycol distearate, ethylene glycol distearate, propylene glycol distearate, polyethylene glycol distearate, and polypropylene glycol distearate.

[0020] Metal fine particles can be uniformly dispersed for a long period of time in dispersions containing various dispersion media without aggregation or sedimentation, but from the viewpoint of the balance between antimicrobial properties, dispersibility, and economic efficiency, it is preferable that the metal fine particles are contained in the dispersion in an amount of 10 mass% or less, particularly 0.001 to 10 mass%, particularly 0.002 to 5 mass%, and particularly 0.01 to 1 mass%. The above content means the proportion of non-volatile components in the dispersion.

[0021] [Ascorbic acid or its derivatives] The ascorbic acid or its derivative used as a stabilizer in the present invention is preferably a low molecular weight compound that can suppress oxidation of metal fine particles and can easily coat the surface of metal fine particles. As described later, when the solvent of the dispersion is water or an aqueous solvent, or when the dispersion is an aqueous paint dispersion, it is preferably a compound that exhibits water solubility.

[0022] Examples of ascorbic acid or its derivatives include ascorbic acid, calcium ascorbate, sodium ascorbate, ascorbic acid-2-glucoside, 2-o-methyl ascorbic acid, 3-o-methyl ascorbic acid, 2-o-ethyl ascorbic acid, 3-o-ethyl ascorbic acid, ascorbic acid-6-palmitate, ascorbic acid-6-stearate, ascorbic acid dipalmitate, and 6-o-palmitoyl ascorbic acid. Examples of ascorbic acid-2-o-phosphate include 6-o-acyl-2-o-α-D-glucopyranosyl-L-ascorbic acid, magnesium ascorbic acid-2-phosphate, ascorbic acid-2-phosphate, sodium ascorbic acid-2-phosphate, ascorbic acid-2-sulfuric acid, potassium ascorbic acid-2-sulfate, ascorbic acid-2-barium sulfate, ascorbic acid-2-sulfate, disodium ascorbic acid-2-sulfate, and trisodium ascorbic acid-2-phosphate. Among the above stabilizers, L-ascorbic acid and 3-o-ethyl ascorbic acid can be preferably used in the present invention from the viewpoints of coating ability on metal fine particles, reducing ability and water solubility.

[0023] [Thickener] The thickener used in the present invention may be any of the conventionally known organic or inorganic thickeners, and even thickeners that tend to promote the oxidation of metal microparticles can be suitably used by using ascorbic acid or its derivatives in combination. Examples of organic thickeners include natural polymers such as dextran, hyaluronic acid, gelatin, collagen, methylcellulose, ethylcellulose, hydroxyethylcellulose, carboxymethylcellulose, soluble starch, and alginates, as well as derivatives thereof, and polymers containing repeating units of vinyl alcohol, vinylpyrrolidone, and acrylic acid. Examples of inorganic thickeners include smectite minerals such as montmorillonite, bentonite, saponite, hectorite, and laponite, and inorganic minerals such as sepiolite. These thickeners may be used alone or in combination of two or more.

[0024] Among these, aqueous (water-soluble or water-dispersible) thickeners are preferred, and polymers or inorganic minerals containing a vinylpyrrolidone unit are particularly suitable. Examples of polymers containing vinylpyrrolidone units include polyvinylpyrrolidone, vinyl acetate-vinylpyrrolidone copolymer, polyvinylpyrrolidone / vinyl acetate / vinyl propionate terpolymer, 2-ethylhexyl acrylate-vinylpyrrolidone copolymer, etc. In this case, the average molecular weight of the copolymer containing a vinylpyrrolidone unit is preferably 10,000 to 5,000,000, more preferably 50,000 to 4,000,000, further preferably 100,000 to 3,500,000, and most preferably 150,000 to 2,000,000. Furthermore, it is preferable for the inorganic thickener to have an average particle size of 100 μm or less. This particle size can be measured using a scanning electron microscope (SEM). Among the above, polyvinylpyrrolidone and montmorillonite are particularly suitable for use in the present invention.

[0025] [Dispersant] The dispersant used in the present invention may be any known dispersant, but is preferably at least one selected from the group consisting of copolymers and low molecular weight compounds having an ionic hydrophilic group and a hydrophobic group. Examples of the copolymer include dispersants having polyester, polyacrylic, polyether, polyoxyalkylene, or the like in the main chain or side chain. Among them, it is preferable to have a hydrophilic block constituted by a polyoxyalkylene skeleton (polyalkylene oxide such as polyethylene oxide or polyethylene oxide-polypropylene oxide), and it is particularly preferable to have a polyoxyethylene skeleton. In the copolymer, the functional group bonded to the main chain skeleton or side chain may be an acidic functional group such as a carboxyl group, an acid anhydride group, a sulfonic acid group, or a phosphoric acid group. The copolymer may also be a wetting / dispersing agent having a star polymer structure or a comb polymer structure having a basic functional group such as an amino group, an imino group, an ammonium salt group, or a heterocyclic group having a basic nitrogen atom together with the acidic functional group. As the copolymer having a polyoxyethylene skeleton, for example, a copolymer of polyoxyethylene (meth)acrylate units or polyoxypropylene (meth)acrylate units or polyethylene-copropylene glycol (meth)acrylate units with styrene-containing units or hydroxyl group-containing units or carboxyl group-containing units, a copolymer of polyoxyethylene alkyl ether units and maleic anhydride units, and a copolymer of polyoxyethylene alkyl ether units, maleic anhydride units and styrene units can be suitably used. The dispersant made of a copolymer has an acid value in the range of 3 to 100 mgKOH / g, preferably 4 to 30 mgKOH / g, and particularly preferably 5 to 20 mgKOH / g. If the acid value is smaller than the above range, the storage stability of the dispersion may be lower than when the acid value is within the above range, while if the acid value is larger than the above range, the water resistance of the coating film may be lower than when the acid value is within the above range.

[0026] The dispersant made of the copolymer preferably has a weight-average molecular weight of at least 1,000. If the weight-average molecular weight of the dispersant is less than 1,000, it cannot be sufficiently sterically hindered by the acidic functional group, or the acidic functional group and the basic functional group. By incorporating a dispersant consisting of the above-mentioned copolymer, the acidic functional groups, or the acidic functional groups and basic functional groups, of the dispersant are firmly adsorbed to the metal microparticles, thereby imparting polarity to the metal microparticles, causing the metal microparticles to repel each other due to their electric charge, and forming steric hindrance due to the presence of modifying groups of a certain length on the surface of the metal microparticles, thereby making it possible for the metal microparticles to be uniformly dispersed in the dispersion medium without agglomeration or sedimentation.

[0027] Examples of the low molecular weight compound having an ionic hydrophilic group and a hydrophobic group include anionic surfactants and cationic surfactants. In other words, in a low molecular weight compound having an ionic hydrophilic group and a hydrophobic group, the ionic hydrophobic group is attracted to the surface of a metal microparticle having a negative zeta potential in a dispersion liquid, so that the ionic hydrophilic group side of the low molecular weight compound faces outward on the surface of the metal microparticle, and such metal microparticles repel each other, resulting in improved dispersibility of the metal microparticles.

[0028] Specific examples of the anionic surfactant include fatty acid soaps such as sodium stearate and sodium dodecanoate, sulfates such as sodium dodecyl sulfate and sodium lauryl sulfate, and sulfonates such as sodium dodecylbenzenesulfonate. Of these, sodium dodecyl sulfate is preferably used. Specific preferred examples of the cationic surfactant include quaternary ammonium salts such as dodecyl ammonium chloride, dodecyl ammonium bromide, dodecyl trimethyl ammonium bromide, dodecyl pyridinium chloride, dodecyl pyridinium bromide, hexadecyl trimethyl ammonium chloride, and hexadecyl trimethyl ammonium bromide. Among these, hexadecyl trimethyl ammonium chloride is preferably used.

[0029] Dispersants that can be suitably used in the dispersion of the present invention include, but are not limited to, DISPERBYK-102, 180, 182, 184, 190, 191, 192, 193, 194N, 199, 2060, 2061, 2090, 2095, 2096, 2155, 154 (manufactured by BYK-Chemie), Sokalan CP9, Lupasol FG, Pluronic PE6400, Pluronic PE6800, Lutropur MSA, Sokalan PA110S, Sokalan CP12S, Sokalan CP13S, Sokalan VA 64P, Lupasol HF, Plurafac LF300, Pluronic RPE1740, Pluronic RPE3110, Degressal SD40 (manufactured by BASF), SC-0505K, AFB-1521, SC-1015F, AKM-0531, and AKM-1511-60 (manufactured by NOF Corp.) can be used, and among these, DISPERBYK-102, 190, and 2060 are particularly suitable.

[0030] The dispersant is preferably contained in an amount of 50 to 1000 parts by mass, particularly 100 to 500 parts by mass, per 100 parts by mass of metal fine particles. If the amount of dispersant is less than the above range, the dispersibility of the metal fine particles will be inferior to that in the above range, while if the amount of dispersant is more than the above range, further improvement in the effect cannot be expected, and there is a risk of poor economic efficiency.

[0031] [Dispersion medium (solvent)] The dispersion of the present invention is preferably made by combining the above-mentioned ascorbic acid or its derivatives, dispersant and thickener, and since ascorbic acid or its derivatives, and thickeners such as polyvinylpyrrolidone and montmorillonite are water-soluble, they can be combined with various types of water such as distilled water, ion-exchanged water, pure water, or a mixed solvent of the above-mentioned various types of water and an amphipathic organic solvent to form a dispersion or paint dispersion, which is excellent in handleability such as coatability. The metal fine particles are uniformly dispersed in the coating film formed by this, making it possible to impart excellent antimicrobial properties. Examples of amphiphilic organic solvents that can be used in combination with water include alcohol solvents such as methanol, ethanol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, t-butyl alcohol, and ethylene glycol; glycol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and diethylene glycol; and ketone solvents such as acetone and methyl ethyl ketone.

[0032] [others] The dispersion liquid of the present invention can be used in combination with other components as necessary, such as antioxidants, surfactants, resins, curing agents, catalysts, polymerization initiators, etc., in addition to the above-mentioned metal fine particles, ascorbic acid or a derivative thereof, thickener, dispersion medium, and dispersant. For example, when the dispersion is used as a water-soluble paint, if it contains a water-dispersible resin such as a carboxyl group-containing polyester resin as a binder resin, it can also contain a curing agent such as an amino resin or a resol-type phenolic resin having a functional group capable of reacting with a carboxyl group in a known formulation.

[0033] (Method of producing antimicrobial dispersion) The metal fine particles constituting the antimicrobial dispersion of the present invention can be prepared by the following production method. (1) First step A polyol solution containing metal fine particles coated with fatty acid and / or ester compound of fatty acid and polyol is prepared by adding fatty acid metal salt to polyol and heating the mixture. The heating temperature is lower than the decomposition start temperature of the fatty acid metal salt used, and the heating and mixing time is preferably 60 to 360 minutes. If the heating temperature is higher than the decomposition start temperature of the fatty acid metal salt, the fatty acid and / or ester compound will not be coated on the metal fine particles, and the metallic copper fine particles may be oxidized. The decomposition start temperature is defined by JIS K 7120.

[0034] The amount of fatty acid metal salt is preferably in the range of 0.1 to 25% by mass per polyol. If the amount of fatty acid metal salt is less than the above range, there is a risk that sufficient antimicrobial properties cannot be imparted to the dispersion liquid compared to the case where the amount is within the above range. On the other hand, if the amount of fatty acid metal salt is more than the above range, there is a risk that the economic efficiency is inferior and the coatability and moldability are impaired compared to the case where the amount is within the above range. Examples of the polyol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, and glycerin, and are appropriately selected in combination with the low-boiling point solvent described below.

[0035] (2)Second process Next, the polyol solution containing the metal fine particles coated with a fatty acid and / or an ester compound of the fatty acid and a polyol is mixed with a low boiling point solvent to prepare a mixed liquid. The low boiling point solvent is preferably added in an amount of 10 to 200% by mass based on the polyol. Examples of low-boiling point solvents include esters such as methyl acetate, ethyl acetate, and butyl acetate, hydrocarbons such as hexane, heptane, toluene, xylene, and cyclohexane, and ketones such as methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone, but ester solvents are preferred, and among them, butyl acetate, ethyl acetate, and methyl isobutyl ketone can be preferably used. It is important that the low-boiling point solvent is not miscible with the polyol, and it is preferable to combine the polyol and the low-boiling point solvent so that the difference in solubility parameter (Sp value) between them is 3 or more. Preferably, when diethylene glycol (Sp value: 12.6) is used as the polyol, butyl acetate (Sp value: 8.4) is used as the low boiling point solvent.

[0036] (3) Third step The mixed liquid is allowed to stand for 30 to 120 minutes at a temperature of 0 to 40° C. to cause phase separation of the polyol and the low-boiling point solvent. When the mixed liquid is phase-separated, the excess fatty acid metal salt, free fatty acid or fatty acid ester compound, or impurities present in the mixed liquid are extracted into the low-boiling point solvent, and the metal particles coated with the fatty acid and / or the fatty acid and polyol ester compound remain in the polyol in a precipitated state. Since the metallic copper particles are sufficiently coated with the ester compound of fatty acid and polyol in the first step described above, it is not necessary to specifically add an ester compound to the low-boiling point solvent, but it may be possible to add one depending on the amount of coating in the first step. Next, the low boiling point solvent is removed from the phase-separated mixed liquid to obtain a solution containing metal fine particles coated with a fatty acid and / or an ester compound of the fatty acid and a polyol in a polyol. The low boiling point solvent can be removed by a conventionally known separation method such as decantation or extraction. The metal fine particle powder can be recovered from the polyol by a conventionally known separation method such as membrane separation, centrifugation, decantation, etc., but is not limited thereto, and is preferably recovered by membrane separation. The separated metal microparticles are thoroughly washed with water or a low-boiling point solvent such as butyl acetate or hexane, and then heated and dried at 40 to 50°C for 60 to 360 minutes to thoroughly remove moisture, thereby obtaining a dry metal microparticle powder with a coating amount of fatty acid and ester compound of 0.1 to 20 mass%.

[0037] (4) Fourth step A dispersant is added to a dispersion medium such as water and mixed, and then the metal fine particle powder is added and mixed. At this time, it is preferable to carry out a dispersion treatment using an ultrasonic disperser, homogenizer, mixer, etc. so that the metal fine particles are uniformly dispersed. Next, ascorbic acid or its derivative is added in the amount described above, and a mixing and dispersion process is performed. Thereafter, water containing a thickener, etc. is added, and further mixing and dispersion processes are performed, thereby obtaining a dispersion liquid containing metal fine particles coated with ascorbic acid or its derivative, and metal fine particles coated with a dispersant. In the present invention, as described above, it is important to add ascorbic acid or its derivative and dispersant to the dispersion liquid and perform sufficient mixing and dispersion treatment before blending the thickener. This makes it possible to coat the surfaces of the metal fine particles with ascorbic acid or its derivative and dispersant in advance, and to obtain a dispersion liquid in which oxidation of the metal fine particles by the thickener is effectively prevented. If desired, the fine metal particle powder coated with ascorbic acid or a derivative thereof and a fatty acid and / or a fatty acid ester can be recovered from this dispersion by using a separation method such as the membrane separation described above.

[0038] [Second manufacturing method] In the first step of the first manufacturing method described above, the same process as in the first manufacturing method is carried out except that a combination of a fatty acid and a metal compound is added instead of a fatty acid metal salt, thereby preparing a dispersion of metal microparticles coated with a fatty acid and / or an ester compound of the fatty acid. Then, by going through the second to fourth steps described above, a dispersion containing metal microparticles, ascorbic acid or a derivative thereof, a thickener, and a dispersant can be obtained, similar to the first manufacturing method.

[0039] [Other manufacturing methods] According to the above-mentioned first and second production methods, the dispersion of the present invention can be efficiently produced, but the dispersion can also be produced by the following method. That is, the polyol solution containing metal fine particles coated with the fatty acid and / or the ester compound of the fatty acid and the polyol obtained in the first step of the first production method described above may be used as it is, and the metal fine particles recovered from this solution may be used to make a dispersion. In this case, the viscosity of the polyol dispersion is high due to the excess fatty acid metal salt, or free fatty acid or ester compound, as well as impurities, and it is difficult to remove the polyol as it is, so the viscosity is reduced by diluting with ethanol or the like, and then the solvent is removed. In addition, a fatty acid metal salt can be heated and reduced in an inert atmosphere, and then ascorbic acid or a derivative thereof can be added and the mixture can be ground and mixed to produce a metal microparticle powder coated with at least ascorbic acid or a derivative thereof. This can then be added to a dispersion medium together with a dispersant and a thickener to form a dispersion liquid.

[0040] (Antibacterial and antiviral agents) The dispersion of the present invention prepared by the above method can be used as an antibacterial or antiviral agent as it is, or the powdered metal microparticles prepared by the above method can be dispersed in the above-mentioned dispersion medium to prepare an antibacterial or antiviral agent. A coating dispersion can be prepared by blending a binder resin and, if necessary, a solvent and a curing agent, and mixing them uniformly, thereby forming an antimicrobial coating film on the surface of a molded article, as described below. The binder resin is preferably added in an amount of 4,000 to 100,000 parts by mass per 100 parts by mass of the metal fine particles.

[0041] (Antimicrobial molded product) The antimicrobial molded article of the present invention has a coating film made of the above-mentioned dispersion or a coating film made of the above-mentioned paint composition on the surface of a molded article such as a plastic molded article such as a resin film, or a fiber molded article such as a nonwoven fabric, woven fabric, or knitted fabric, and can be produced by spraying or applying the above-mentioned dispersion or paint dispersion to the surface of the molded article to form a coating film, or by further baking and drying to form and fix a coating film. EXAMPLES

[0042] <Synthesis of metallic copper nanoparticles> The diethylene glycol was adjusted to 2.5% by mass of copper stearate (II), and heated and stirred. After heating for 2 hours from the point where the temperature reached 190°C, the mixture was cooled to 110°C, butyl acetate was added, and stirred for about 1 minute. The mixture was then left to stand to separate the diethylene glycol layer and the butyl acetate layer, and the butyl acetate layer was removed to obtain a diethylene glycol solution containing metallic copper particles. This diethylene glycol dispersion was suction filtered through a membrane filter with a pore size of 10 μm, washed with ethanol, and dried at 50°C for 2 hours to obtain metallic copper particle powder.

[0043] (Production Example 1) 0.05 g of DIPERBYK-190 (manufactured by BYK-Chemie, acid value 10 mgKOH / g) as a dispersant was added to pure water to prepare 25 g of a 0.2 mass% dispersant solution. Next, 0.05 g of the metallic copper microparticle powder prepared above was added to the dispersant solution, and ultrasonic treatment was performed for 10 minutes. After that, L-ascorbic acid was added so that the amount was 200 parts by mass per 100 parts by mass of metallic copper microparticles, and ultrasonic treatment was performed for another 10 minutes. Next, 25 g of pure water was added, and the mixture was stirred for 10 minutes to obtain a metallic copper microparticle dispersion.

[0044] (Production Example 2) A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that the ratio of L-ascorbic acid was changed to 500 parts by mass per 100 parts by mass of the metallic copper microparticles.

[0045] (Production Example 3) A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that the ratio of L-ascorbic acid was changed to 1,000 parts by mass per 100 parts by mass of the metallic copper microparticles.

[0046] (Production Example 4) A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that the ratio of L-ascorbic acid was changed to 100 parts by mass per 100 parts by mass of metallic copper microparticles.

[0047] (Production Example 5) A metallic copper fine particle dispersion was prepared in the same manner as in Production Example 1, except that L-ascorbic acid was not added.

[0048] (Production Example 6) A metallic copper fine particle dispersion was prepared in the same manner as in Production Example 3, except that L-ascorbic acid was changed to another stabilizer, citric acid.

[0049] <Method for measuring zeta potential> The zeta potential was measured using an ELSZ-2000ZS Zeta Potential / Particle Size / Molecular Weight Measurement System manufactured by Otsuka Electronics Co., Ltd. The measurement was performed using a standard cell unit at a measurement voltage of 60 V. If the absolute value of the zeta potential changes compared to Production Example 5, in which no L-ascorbic acid was added, this indicates that L-ascorbic acid is acting on the surface of the metallic copper particles. Measurements were performed for Production Examples 1 to 6. The results are shown in Table 1.

[0050] [Table 1]

[0051] Example 1 A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that after ultrasonic treatment, 25 g of pure water was replaced with 25 g of a solution containing 2 mass % montmorillonite (Kunipia G4, manufactured by Kunimine Industries Co., Ltd.).

[0052] Example 2 A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that after ultrasonic treatment, 25 g of a solution containing 1 mass % polyvinylpyrrolidone (PVPK90 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added instead of 25 g of pure water.

[0053] Example 3 A metallic copper microparticle dispersion was prepared in the same manner as in Production Example 1, except that after ultrasonic treatment, the 25 g of pure water was replaced with 25 g of a solution containing 1 mass % of vinylpyrrolidone / vinyl acetate copolymer (DSP PVP / VA E-735, manufactured by Gokyo Food & Chemical Co., Ltd.).

[0054] Example 4 A metallic copper fine particle dispersion was prepared in the same manner as in Example 1, except that 200 parts by mass of L-ascorbic acid was replaced with 500 parts by mass of 3-o-ethyl ascorbic acid (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0055] Example 5 A metallic copper fine particle dispersion was prepared in the same manner as in Example 1, except that sodium dodecyl sulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of DISPERBYK-190.

[0056] Example 6 A metallic copper fine particle dispersion was prepared in the same manner as in Example 1, except that in Production Example 1, DISPERBYK-190 was replaced with hexadecyltrimethylammonium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0057] Comparative Example 1 A dispersion was prepared in the same manner as in Example 1, except that L-ascorbic acid was not added.

[0058] Comparative Example 2 A dispersion was prepared in the same manner as in Example 2, except that L-ascorbic acid was not added.

[0059] Comparative Example 3 A dispersion was prepared in the same manner as in Example 3, except that L-ascorbic acid was not added.

[0060] Comparative Example 4 A dispersion liquid was prepared in the same manner as in Example 2, except that L-ascorbic acid was changed to citric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0061] <Evaluation of dispersibility of metal particles in dispersion liquid> The prepared dispersion was stored at room temperature, and the dispersibility of the metal particles was evaluated. The dispersion in which no precipitation of metal particles occurred even after one month after preparation was marked with ⊚, the dispersion in which precipitation of metal particles occurred one month after preparation was marked with ◯, and the dispersion in which precipitation of metal particles occurred one day after preparation was marked with ×. The evaluation was performed using Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 2.

[0062] <Appearance evaluation of dispersion liquid> When no stabilizer is used, the dispersion is confirmed to turn brown or light blue over time, which means that the metallic copper particles in the dispersion are oxidized or ionized, that is, the antimicrobial performance is lost. Therefore, whether the oxidation of metallic copper particles can be suppressed by using the stabilizer of the present application in combination was confirmed by the following method. The prepared dispersion was left to stand at room temperature for one month, and the color of the dispersion was visually confirmed. Dispersions that did not change in color were rated as ◯ (metal layer fine particles were maintained), and those that changed in color to brown or light blue were rated × (metal copper fine particles were oxidized). Confirmation was performed using Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 2.

[0063] <Measurement of the crystal structure of metallic copper particles in a dispersion> The prepared dispersion was left to stand at room temperature for one month. The metallic copper particles contained in the dispersion were then completely precipitated by centrifugation. The crystal structure of the metallic copper particles contained in the collected solids was measured using an X-ray diffractometer Smart Lab manufactured by Rigaku Corporation, and the metallic copper ratio was calculated from the results using the following calculation method. Metallic copper ratio (%)= Integral intensity of metallic copper / (Integral intensity of metallic copper + Integral intensity of cuprous oxide + Integral intensity of copper oxide) x 100 From the calculation, those in which the metallic copper ratio did not change immediately after preparation were marked with an ◯, and those in which the metallic copper ratio changed immediately after preparation were marked with an X. This was confirmed using Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 2.

[0064] [Table 2]

[0065] <Antiviral evaluation> (Method of application to nonwoven fabric) The prepared dispersion was applied to an unprocessed nonwoven fabric with a brush, and then dried in a dryer at 80° C. for 5 minutes to obtain a nonwoven fabric (molded product) on which metallic copper particles were fixed.

[0066] <Method for evaluating the antiviral properties of nonwoven fabric> The test was carried out according to JIS L 1922. (1) Host cells are infected with the virus, cultured, and then centrifuged to remove cell debris to obtain a virus suspension. (2) The virus suspension in (1) above is diluted 10-fold with sterile distilled water to prepare the test virus suspension. (3) Inoculate 0.2 ml of the test virus suspension onto a 0.4 g test piece of nonwoven fabric. (4) After leaving the specimen at 25°C for 2 hours, add 20 ml of SCDLP medium, mix with a vortex mixer, and wash out the virus from the specimen. (5) The viral infectivity is measured using the plaque assay, and the antiviral activity value is calculated. (6) If the antiviral activity value is 3.0 or higher, it can be determined that the product has sufficient antiviral properties against that virus.

[0067] The dispersions of Example 2, Example 1, and Comparative Example 1, which had been left to stand for one month, were applied to nonwoven fabrics (Example 7, Example 8, Comparative Example 5). The antiviral properties of the resulting nonwoven fabrics were then evaluated. Antiviral activity values ​​of less than 3 were marked with "x," and values ​​of 3 or more were marked with "o." The results are shown in Table 3.

[0068] [Table 3] [Industrial Applicability]

[0069] The antimicrobial dispersion of the present invention can impart antimicrobial properties to textile products such as paper products, masks, wet tissues, air conditioner filters, air purifier filters, clothing, work clothes, curtains, carpets, automotive parts, packaging parts, freshness-preserving materials, sheets, towels, bath mats, diaper covers, stuffed toys, slippers, shoe insoles, and cleaning supplies such as wipers, by directly applying the dispersion to or impregnating the textile products, and can be used as it is as an antibacterial and antiviral agent. Furthermore, by using an aqueous solvent as the dispersion medium of the dispersion, it is possible to use it as a diluent for the aqueous composition, or by including a binder resin in the dispersion, it is possible to obtain a molded article having an antimicrobial coating film on the surface. Furthermore, the material can be used for medical equipment, packaging films for medical equipment, waste containers, garbage bags, wall materials and floor materials in nursing homes or public facilities such as hospitals and schools, wax coating materials, and vomit disposal equipment. Furthermore, in addition to sanitary products, the present invention can also be applied to films, metal plates, glass plates, marine paints, heat exchanger fins, ceramic products such as tableware, rubber products, metal products such as faucets, additives for humidifiers, liquid detergents, ion adsorbents, deodorants, etc., and can impart antimicrobial properties to them.

Claims

1. A dispersion liquid containing metal fine particles, a dispersant, and a thickener, At least a part of the surface of the metal fine particles is coated with ascorbic acid or a derivative thereof, The dispersion liquid, wherein the dispersant is at least one selected from the group consisting of a copolymer and a low molecular weight compound having an ionic hydrophilic group and a hydrophobic group.

2. 2. The dispersion according to claim 1, wherein the metal fine particles are copper or a copper compound, silver or a silver compound, or a complex thereof.

3. 3. The dispersion according to claim 1, wherein the thickener is an aqueous thickener and is a polymer or an inorganic mineral containing a vinylpyrrolidone unit.

4. 3. The dispersion according to claim 1, wherein the ascorbic acid or a derivative thereof is contained in an amount of 10 parts by mass or more per 100 parts by mass of the metal fine particles.

5. 3. The dispersion according to claim 1, wherein the thickener is contained in an amount of 50 to 5,000 parts by mass based on 100 parts by mass of the metal fine particles.

6. 3. The dispersion according to claim 1, wherein the dispersant comprising the copolymer has a polyoxyethylene skeleton.

7. 3. The dispersion according to claim 1, wherein the dispersant comprising a low molecular weight compound having an ionic hydrophilic group and a hydrophobic group is an anionic surfactant or a cationic surfactant.

8. 3. The dispersion according to claim 1, wherein the dispersant is contained in an amount of 50 to 1000 parts by mass based on 100 parts by mass of the metal fine particles.

9. 3. The dispersion according to claim 1, wherein the metal particles are coated with a fatty acid and / or a fatty acid ester.

10. 3. The dispersion according to claim 1, wherein the content of the metal particles is 0.001 to 10% by mass.

11. 3. An antibacterial and antiviral agent comprising the dispersion according to claim 1 or 2.

12. 3. An antimicrobial molded article comprising a layer of the dispersion according to claim 1 or 2 on the surface of the molded article, which is made of any one of a plastic molded article, a nonwoven fabric, a woven fabric, and a knitted fabric.

13. The antimicrobial molded article according to claim 12, which has an antiviral activity value of 3.0 or more after one month.

14. 3. A method for producing a dispersion liquid according to claim 1 or 2, characterized in that metal fine particles, ascorbic acid or a derivative thereof, and a dispersant are added and mixed into a dispersion medium to prepare a dispersion liquid containing metal fine particles having at least a portion of their surface covered with the ascorbic acid or a derivative thereof, and then a thickener is added and mixed into the dispersion liquid.

Citation Information

Patent Citations

  • Kachoshikikuranpu

    JP1976094185A

  • Antiviral coating film

    JP2015205998A

  • Silver ultrafine particle-containing dispersion liquid and method for producing the same

    JP2017128809A

  • Dispersion liquid, method for producing the same, and copper compound particles

    JP2018100255A